Pengaruh Lingkungan Kerja Terhadap Semangat Kerja Pegawai Puskesmas Wawo Kabupaten Bima - Intan Rahmawati; Mulyadin Mulyadin (Jurnal Riset dan Inovasi Manajemen, 2023)
This research is an associative research that aims to determine the effect of the work environment on the morale of the employees of the Wawo Public Health Center, Bima Regency. This research was conducted at the Wawo Public Health Center, Bima Regency. The research instrument used was a questionnaire containing a number of statements with a Likert scale measurement. The population used was all employees of the Wawo Public Health Center, Bima Regency, with 119 employees. The sampling technique used random sampling with a total sample of 44 employees. Data collection techniques used in this research are observation, documentation, literature study. The data analysis technique used is validity test, reliability test, simple linear regression, correlation coefficient, coefficient of determination, t test. The results showed that the work environment had an effect on the morale of the employees of the Wawo Public Health Center, Bima Regency. The magnitude of the influence of the work environment on employee morale is 41.8%.